2010
DOI: 10.4142/jvs.2010.11.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sperm quality traits and field-fertility of porcine semen

Abstract: An investigation involving seven boars, active in artificial insemination, and 1,350 multiparous sows was conducted at a private farm and aimed at examining the relationship between sperm quality traits and boar fertility in terms of farrowing rate and litter size. This experiment was done for 6 months. The semen samples were evaluated for subjective sperm motility and concentration. Ejaculates with at least 1 × 108 sperm/mL and 70% sperm progressive motility were extended with a commercial medium to 30 × 106 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 20 publications
(24 reference statements)
0
57
1
3
Order By: Relevance
“…While several studies have used samples from bulls and humans (Januskauskas et al, 2003;Bungum et al, 2004;Lucio et al, 2016), few have correlated sperm morphology and chromatin instability in swine (Saravia et al, 2007;Tsakmakidis et al, 2010). Further, many studies that correlated morphological data with chromatin instability did not distinguish normal cells from those with cytoplasmic droplets, therefore, it is not possible to determine whether the presence of cytoplasmic droplets is related to chromatin instability.…”
Section: Introductionmentioning
confidence: 95%
“…While several studies have used samples from bulls and humans (Januskauskas et al, 2003;Bungum et al, 2004;Lucio et al, 2016), few have correlated sperm morphology and chromatin instability in swine (Saravia et al, 2007;Tsakmakidis et al, 2010). Further, many studies that correlated morphological data with chromatin instability did not distinguish normal cells from those with cytoplasmic droplets, therefore, it is not possible to determine whether the presence of cytoplasmic droplets is related to chromatin instability.…”
Section: Introductionmentioning
confidence: 95%
“…Although the relationship between sperm head dimensions and chromatin status remains controversial, many of the studies reported no relationship between them (Saravia et al, 2007;Gassuto et al, 2011). Aiming at improving the predictive value of semen analysis, earlier investigations supported a relation between fi eld fertility and chromatin integrity after the combination of sperm traits such as live normal spermatozoa and stability of the deoxyribonucleic acid complex (BoeHansen et al, 2008;Tsakmakidis et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, the high farrowing rate may not always be relative to high litter size. Moreover, weak correlations between farrowing rate and litter size were found in other studies, indicating that these traits may be affected differently by the semen quality of the boars (Tsakmakidis et al, 2010;Juonala et al, 1998).…”
Section: Dead Sperm Live Spermmentioning
confidence: 95%
“…After this assessment, two sperm populations were identified: live green-stained sperm (SYBR-14 + /PI -); and dead red-stained sperm (SYBR-14 -/PI + ). Sperm morphology was determined microscopically after staining the semen samples with eosin nigrosin stain on a slide (Tsakmakidis et al, 2010). Briefly, 7µL of boar semen was added to 20µL eosin nigrosin staining solution in a 0.6 mL micro-centrifuge graduated tube and mixed gently.…”
mentioning
confidence: 99%